New findings of Theophilea subcylindricollis (Coleoptera: Cerambycidae) in Serbia (Acta Entomologica Serbica, 2013)
Theophilea subcylindricollis Hladil, 1988 has been recorded in eastern parts of central Europe, namely Kazakhstan, Russia, Ukraine, Moldova, Slovakia, Hungary and Romania (Hoskovec & Rejzek 2009; Löbl & Smetana 2010). It is interesting that neither Serbia (Pil & Stojanović, 2009) nor the Czech Republic (Holomčik, 2013) are listed in Fauna Europaea (Audisio, 2013) although, admittedly, the species was discovered in those two countries only recently.